Preventing war and promoting peace a guide for health professionals - Wiist, William H.; White, Shelley K. (Cambridge University Press, 2017)
"Preventing War and Promoting Peace: A Guide for Health Professionals is an interdisciplinary study of how pervasive militarism creates a propensity for war through the influence of academia, economic policy, the defense industry, and the news media. Comprising contributions by academics and practitioners from the fields of public health, medicine, nursing, law, sociology, psychology, political science, and peace and conflict studies, as well as representatives from organizations active in war prevention, the book emphasizes the underlying preventable causes of war, particularly militarism, and focuses on the methods health professionals can use to prevent war. Preventing War and Promoting Peace provides hard-hitting facts about the devastating health effects of war and a broad perspective on war and health, presenting a new paradigm for the proactive engagement of health professions in the prevention of war and the promotion of peace"--